Investigating the influence of heterocyclic Schiff bases as a biofuel additive on combustion, performance and emissions - Beşir Dağ; Selman Aydın; Ramazan Şener (Case Studies in Thermal Engineering)
The growing need for cleaner and more efficient energy sources has driven extensive research into biofuels and their additives to improve combustion performance and reduce emissions. This study investigates the potential impact of heterocyclic Schiff bases as biofuel additives, exploring their effects on combustion efficiency, engine performance, and emissions characteristics in compression ignition engines. The research aims to enhance fuel efficiency and reduce emissions by leveraging the unique chemical properties of Schiff bases. Heterocyclic Schiff bases, known for their diverse chemical properties, offer a novel avenue for enhancing the combustion properties of fuels. 4-Aminoantipyrine (AAP) Schiff base was synthesized as a fuel additive. The prepared AAP Schiff base was mixed homogeneously within a mixture of ethanol before being incorporated into diesel. The different blends, such as 90 % diesel +10 % ethanol (D90E10) and 90 % diesel + 10 % ethanol + 100 ppm AAP (D90E10-AAP), were prepared for the experiments. Utilizing an eddy current dynamometer, the combustion properties of fuel blends were systematically compared against diesel within a compression ignition engine operating spanning three distinct BMEP levels. Fuel additives improve the emissions and performance of the engine. In terms of cylinder pressure, knock density and mean gas temperature, it was determined that the fuel with novel additive D90E10-AAP results in improvements to diesel. The study is expected to contribute to the existing body of knowledge on this topic and provide insights into the potential applications of AAP Schiff base as a biofuel additive in the automotive industry.